MOTIF PENGGUNAAN MEDIA SOSIAL ð• OLEH REMAJA DI DUSUN SUMBER BARAT DESA SUMBERJOSARI KECAMATAN KARANGRAYUNG KABUPATEN GROBOGAN - Mahendra, Arasyid Yuda; Suryo S, Herning; Siswanta, Siswanta (Solidaritas, 2024)
One product of technological advancement is the internet, which facilitates the rapid global dissemination of information. A notable outcome of this is sosial media, which has transformed the ways we communicate and interact. An example of a sosial media platform with a high number of users is ð•. The aim of this study is to describe the motives behind the use of ð• among teenagers in Dusun Sumber Barat, Sumberjosari Village, Kecamatan Karangrayung, Kabupaten Grobogan. The theoretical framework of this research focuses on sosial media theory, new media theory, uses and gratification theory and also individual media use theory as outlined by McQuail, including information motives, self-identity, sosial integration, and entertainment. This study employs a qualitative descriptive method, utilizing data collection techniques such as interviews, observation, and documentation. Purposive sampling is used to select the research participants. Data analysis is conducted based on the framework developed by Miles and Huberman. The results of this study reveal that the motives for using the sosial media platform ð• among teenagers in Dusun Sumber Barat are varied. These include seeking information, self-expression, sosializing and discussing, finding entertainment, and using ð• as a business platform. The functionality of ð• enables teenagers to build sosial networks, explore personal interests, develop their digital identities, and discover business opportunities.